Changes in brain regions associated with food-intake regulation, body mass and metabolic profiles during acute antipsychotic treatment in first-episode schizophrenia. Issue 2 (30th August 2015) - Emsley, Robin; Asmal, Laila; Chiliza, Bonginkosi; du Plessis, Stefan; Carr, Jonathan; Kidd, Martin; Malhotra, Anil K; Vink, Matthijs; Kahn, Rene S.
Abstract: We investigated whether morphological brain changes occurred in brain regions associated with body-weight homeostasis during acute antipsychotic treatment, and if so, whether they were related to changes in body mass and metabolic profile. Twenty-two antipsychotic-naive patients with first-episode schizophrenia received either risperidone long acting injection or flupenthixol decanoate over 13 weeks and were compared by structural MRI with 23 matched healthy volunteers at weeks 0, 4 and 13. Images were reconstructed using freesurfer fully-automated whole brain segmentation . The ventral diencephalon and prefrontal cortex were selected to represent the homeostatic and hedonic food intake regulatory systems respectively. Body mass was measured at weeks 0, 7 and 13 and fasting glucose and lipid profiles at weeks 0 and 13. Linear mixed effect models indicated significant group ⁎ time interactions for the ventral diencephalon volumes bilaterally. Ventral diencephalon volume reduction was strongly correlated bilaterally with body mass increase and HDL-cholesterol reductions, and unilaterally with blood glucose elevation. There were no significant changes in prefrontal cortical thickness. These findings implicate the ventral diencephalon, of which the hypothalamus is the main component, in the acute adipogenic and dyslipidaemic effects of antipsychotic medication. Highlights: Ventral diencephalon volume reduction was significantly correlated with body mass increase. Ventral diencephalon volume reduction was significantly correlated bilaterally with HDL reduction and LDL increase, and unilaterally with fasting blood glucose. There were no significant correlations between change in prefrontal cortex thickness and body mass or metabolic indices.